Kajian Yuridis Terhadap Perkawinan dibawah Umur - Jakobus A. Rahajaan; Sarifa Niapele (Univiversitas Dr. Djar Wattiheluw, 2021)
This research is in the form of a juridical study of underage marriage. Using the normative legal research method, namelyanalyzing the provisions of the articles of laws and regulations related to the minimum age limit for a person who can be grantedpermission to have a marriage. The results of the research obtained are as follows: According to article I of Law Number 16 of 2019 concerning Marriage which amends Article 7 paragraph (1) of Law no. 1 of 1974, requires that the marriage is legal, if permitted by the parents of the parties, if the age of the prospective bride and groom has reached 19 years. On the other hand, the provisions of the Compilation of Islamic Law (KHI) article 15 paragraph (1), have not revised the age limit of 19 years. This can lead to polemics in society that have the potential to lead to misinterpretation or ambiguity that can lead to unlawful practices, namely underage marriage. Furthermore, in paragraph (2) Article 7 of the Marriage Law Number 1974 as amended by Law Number 16 of 2019, provides space for underage marriages, namely in the form of dispensation for underage marriages. The weaknesses of this statutory regulation must be addressed immediately by revising article 15 paragraph (1) of the KHI, as well as the provisions of Article 1 of Law Number 16 of 2019, namely the provisions of Article 7 paragraphs (2) and (3), regarding the dispensation of underage marriages.